2020
DOI: 10.1111/1440-1681.13245
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐pinene promotes osteoblast differentiation and attenuates TNFα‐induced inhibition of differentiation in MC3T3‐E1 pre‐osteoblasts

Abstract: Alpha‐pinene (α‐pinene) is an organic compound, found in the oils of many species of coniferous trees, especially pine. α‐Pinene reportedly has antioxidant and anti‐inflammatory activities; however, its effects on osteoblasts are unknown. This study investigated the effects of α‐pinene on osteoblast differentiation and tumour necrosis factor‐alpha (TNFα)‐induced inhibition of osteogenesis. Culture in control or osteogenic medium containing α‐pinene increased osteogenic marker expression. Alkaline phosphatase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Moreover, it stimulated apoptosis in mature osteoclasts in vitro [ 26 ]. In other studies, it was shown that some terpenes (e.g., limonene, alpha-pinene) stimulated osteoblast proliferation and differentiation, which is similar to anabolic drug action used in the treatment of osteoporosis [ 22 , 27 , 28 , 29 ]. In vitro studies revealed that limonene induced osteoblastic differentiation of the murine myoblasts (C2C12) (concentration: 2.5 µM) and murine preosteoblasts (MC3T3-E1) (concentration: 0.01–1 μM) [ 27 ].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, it stimulated apoptosis in mature osteoclasts in vitro [ 26 ]. In other studies, it was shown that some terpenes (e.g., limonene, alpha-pinene) stimulated osteoblast proliferation and differentiation, which is similar to anabolic drug action used in the treatment of osteoporosis [ 22 , 27 , 28 , 29 ]. In vitro studies revealed that limonene induced osteoblastic differentiation of the murine myoblasts (C2C12) (concentration: 2.5 µM) and murine preosteoblasts (MC3T3-E1) (concentration: 0.01–1 μM) [ 27 ].…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, limonene (0.01–1 μM) decreased methylglyoxal-induced endoplasmic reticulum (ER) stress and autophagy in the MC3T3-E1 cell line [ 28 ]. Another monoterpene, α-pinene (50 μM), also stimulated the differentiation and mineralization process of osteoblasts in the MC3T3-E1 cells [ 29 ]. There are also reports indicating that cinnamaldehyde prevented osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has an antithrombotic effect (Yang, Zhou et al 2011) [13], stimulates cytoprotective activity against H 2 O 2 -(Porres, Burgos, et al, 2015), (Halliwell 1992) [14,15]. It has anti-inflammatory (Falk, Hagberg, et al, 1990) [16], analgesic (Kim, Lee, et al 2015) [17], (Rufino, Ribeiro, et al 2014) [18], antioxidant properties, (Min, Son, et al, 2020) [19], as well as an expectorant and phlegm-dissolving effect, being a natural support in upper respiratory tract infections with runny nose and cough. In combination with eucalyptus oil, it allows you to perfectly unplug a blocked nose.…”
Section: What Are Essential Oils -Alpha and β-Pinenementioning
confidence: 99%
“…The α-pinene, with the chemical name of 2,6,6-trimetheylbicyclo [3.1.1] hept-2-ene, is a bicyclic monoterpene molecule found in various plants, including camphor, rosemary, and pine [6,7]. Recently, α-pinene was also been found to be presented in the highland barley Baijiu [8].…”
Section: Introductionmentioning
confidence: 99%